Characteristics of Urban Poverty Case Study in Sangkrah, Surakarta City - Astuti, Wahyuni Apri (Forum Geografi, 1998)
This research was intended to analyze on the characteristics of a poor household. The number of respondents in this research was 68 respondents who consisted of the poor households. The Â what their characteristics were. To analyze data, the researcher used a descriptive analysis with the concentration on understanding from the researched community. This research made an effort to implement a poor community based approach in the urban area including understanding problems, and characteristics with the method of the poor community based participants. The result of this research indicated that the characteristics of the poor household included: their job was subject to changing the season and dependent on consumerâs need and want, a tendency to deviate from a law, the old and housewives and were involved to make a living, spending an inappropriate income, their survival dependend on the other people; their children were uneducated; they had not got a house and rented the house for a long time; and they could merely utilize the limited social failities.